Antioxidant and Antiglycation Properties of Seventeen Fruit Teas Obtained from One Manufacturer - Izabela Zieniewska; Anna Zalewska; Małgorzata Żendzian-Piotrowska; Jerzy Robert Ładny; Mateusz Maciejczyk (Applied Sciences, 2020)
The antioxidant activity of teas depends on the type and quality of the ingredients used in the process of tea production, location of the crops, and manner of the raw material processing. Our study is the first to compare the antioxidant and antiglycation properties of seventeen fruit teas obtained from one manufacturer. We evaluated three different brewing times (3, 5, and 10 min) and two brewing temperatures (70 and 100 °C). We demonstrated that infusions with the longest brewing time reveal the highest antiradical activity, while increased brewing temperature does not significantly affect the assessed parameters. The best antioxidant properties were obtained for the teas made from lemon balm with pear, forest fruits, cranberry with pomegranate, raspberry, and raspberry with linden. Fruit teas owe their high antioxidant activity to the presence of polyphenolic compounds in infusions. Extracts from fruit teas also diminish the oxidation and glycation of albumin in vitro, observed as a decrease in the fluorescence of aromatic amino acids and advanced glycation (AGE) and oxidation (AOPP) protein products levels. In conclusion, in order to prepare fruit teas with the best antioxidant properties, a longer extraction time is needed. The health-promoting properties of dried fruit infusions can be modified by changing the qualitative and quantitative composition of the ingredients.